The dose characteristics of low kV intraoperative x-ray source using Gafchromic EBT 3 film - Kanphet, Jaruek; Tawonwong, Tanawat (Journal of Thai Association of Radiation Oncology, 2024)
Background: The INTRABEAM device is an intraoperative radiotherapy (IORT) system used in conjunction with surgery. It delivers a high radiation dose directly to cancer cells, with the radiation evenly distributed in all directions in a spherical pattern. Objective: To study the radiation dose distribution characteristics from a 50 kV X-ray source of the INTRABEAM, Intra-Operative radiotherapy (IORT) machine, and the efficiency of radiation absorption of the lead sheet using Gafchromic EBT3 film. Materials and methods: The experiment is divided into four stages as follows: 1) Creating a calibration curve using Gafchromic EBT3 film. 2) The measured depth dose and the distribution of radiation using Gafchromic EBT3 film. 3) The evaluation of the lead shielding effectiveness on a breast phantom to prevent radiation hazards. 4) The radiation dose measurement around the operating room during radiation delivery using a survey meter. Results: The results are divided into 4 parts. 1) The calibration curve showed that the optical density (OD) increased linearly with the radiation dose, and then plateaued. The red light spectrum was the most sensitive to radiation, maintaining linearity up to approximately 250 cGy. Therefore, red light was used to read the film in all experiments. 2) The depth dose profile resembled the manufacturer’s specifications, with slight deviations near the applicator surface and stabilization at around 1 cm depth. The radiation dose distribution from the applicator cone’s center was uniform across all planes along both the X and Y axes, indicating an isotropic radiation pattern. 3) Lead sheets were able to absorb up to 89% of the radiation dose. 4) The highest radiation dose was detected near the INTRABEAM device, with a maximum of 34 mR/hr. The radiation dose decreased with increasing distance, measuring below 1 mR/hr outside the operating room and at the staff positions. Conclusion: The depth dose measured using Gafchromic EBT3 film is consistent with the depth dose data provided by the manufacturer. The distribution of radiation from the edge of the applicator demonstrates isotropic distribution. The lead sheets have high efficiency in absorbing radiation. The radiation levels around the operating room are within safe limits for personnel operating the device, ensuring safety both inside and outside the operating room during patient treatment.